Right to be Forgotten: Harmonizing Privacy with The Right to Freedom of Speech and Expression in India - Rajat, Anuprash; Grewal, Upendra (Journal of Neonatal Surgery, 2025)
The Internet noway forgets one of the numerous advantages of the internet, which has come a agony for numerous. Any information uploaded on the internet by any party remains there till its access has explicitly been confined or it had been canceled. The Right to be forgotten refers to the capability of individualities to abolish, limit, delink, cancel, or correct particular information on the Internet that's deceiving, disturbing, inapplicable, or anachronistic. The Right to be forgotten is a right that allows the persons affected to get the said data canceled or deleted. It reflects a claim that an existent can get specific data deleted to insure no other party can trace it. The right primarily entitles the individual to have information vids or photos deleted from the internet to insure that hunt machines can not find them. The explanation behind the idea is that people shouldn’t be affected by any information about a once event that they did by mistake or had been cleared of it. This right is abecedarian moment, as once any content is participated on social media, it gets to a broad followership. The said right were established through a directive in the European Union and has been explicitly mentioned as a right under the GDPR 2018; still, that is n't devoid of issues. In India, there has been no substantiation of the said right; still, the state has drafted a bill that provides for the erasure and exposure of applicable data, but the same is still in the timber. The Judiciary itself has not cleared the air for the said right, and it remains a slate space. The European governance has inspired the Indian legislation legislated to apply the right. The Indian script will be a clash between the right to sequestration and the right to freedom of speech. It has also been criticised as it can be used as a suppression tool. Through this exploration paper, we shall be looking at the development of the said right and how, in the Indian environment, this right can be applied.